Legal Protection Of Trademarks In The Business Competition Of The Fashion Industry In Indonesia - Wicaksono, Bagus Putra; Astutik, Sri; Cornelis, Vieta I (PT. Anagata Sembagi Education, 2025)
Legal protection of trademarks in the fashion industry has a crucial role in maintaining the identity and competitiveness of products in the midst of increasingly fierce business competition. This study aims to analyze the effectiveness of existing regulations in protecting trademark rights and identify challenges in their implementation in the digital era. The research method used is a normative juridical approach by analyzing laws and regulations, court decisions, and policies related to trademark protection. The results of the study show that although Law Number 20 of 2016 concerning Trademarks and Geographical Indications has provided a comprehensive legal framework, its implementation still faces obstacles, especially in terms of supervision of trademark infringement, lack of legal awareness among business actors, and suboptimal brand protection in digital trade. Strengthening legal protection requires a revision of regulations that are more adaptive to technological developments and strengthening dispute resolution mechanisms, including the implementation of online mediation platforms to reduce the burden of litigation. In addition, optimizing the role of the Directorate General of Intellectual Property (DJKI) through digitization of brand registration and technology-based supervision such as blockchain is a strategic step in increasing the effectiveness of legal protection. Legal education for business actors and the public must also be improved to build awareness of the importance of brand protection as a business asset with economic value. A more holistic and collaborative approach between governments, industry associations, and non-governmental organizations, the legal protection system for trademarks can be more effective, innovative, and in accordance with the dynamics of the fashion industry in the era of globalization.